Comparison of the effects of cold water immersion and percussive massage on the recovery after exhausting eccentric exercise: A three-armed randomized controlled trial - Heinke, Lars; Javanmardi, Sasha; Rappelt, Ludwig; Konrad, Andreas; Schleip, Robert; Knicker, Axel J.; Freiwald, Jürgen; Baumgart, Christian (Frontiers in Physiology, 2024)
Athletic training requires both challenging stimuli for adaptation and sufficient recovery for improved performance. While cold water immersion (CWI) is already a popular recovery method, handheld percussive massage (PM) devices have also gained popularity in recent years. This study aims to assess the effects of CWI and PM on performance recovery after strenuous eccentric exercises compared to a passive rest (PR) control condition. Thirty-four healthy physically active participants (9 females, 25 males) were randomly divided into three groups: CWI (n=11), PM (n=11), and passive rest (PR) (n=12). They underwent an exhausting eccentric exercise protocol and different measurements at six time points (baseline, POST1, POST2, POST24, POST48, and POST72) over the time course of 72 hours. These included subjective assessments of muscle soreness and perceived stiffness as well as measures of skin temperature, leg volume, creatine kinase activity, and three different jump tests. The eccentric exercise protocol consisted of 15 min downhill running (slope: -12%, speed: 10 km/h) and 3 sets of successive depth jumps (dropping height: 0.5 m) until individual exhaustion. After POST1 measurements, participants received 12 min of either CWI (11 ± 0,5°C), PM (40 Hz) or PR (supine posture). No significant group effects were found for the number of depth jumps performed during the exhaustion protocol. All jump tests displayed a significant group × time interaction effect. Post-hoc analysis indicated significant lower jump heights in ΔPOST2 between CWI and both PM and PR. No other significant group effects were observed at any time point. No significant group × time interaction effects were noted for CK, leg volume, and soreness. The perceived stiffness showed significant group × time interaction effect. Post-hoc analysis revealed a significant decrease in stiffness for PM compared to PR at ΔPOST2. Neither CWI nor PM showed any significant improvement in performance recovery over the 72-hour period following strenuous eccentric exercise compared to PR. CWI showed an immediate performance decline which may be attributed to a cold-related reduction in motor nerve conduction velocity.